Sustainable Marketing: Integrating Green Marketing Practices into Marketing Strategy - Nurjaman, Kadar (Global Writing Academica Researching and Publishing, 2024)
This study aims to explore the impact of Green Marketing practices on the financial performance of companies in Indonesia, focusing on variables such as Environmental Practices, Consumer Knowledge, and Company Commitment. The research method used involves quantitative analysis by collecting data through questionnaires distributed to managers and staff in the banking sector. The data obtained were then analyzed using descriptive and inferential statistical techniques, including validity, reliability, and direct effect hypothesis testing. The results of the study indicate that Company Commitment has the most significant influence on Financial Impact, followed by Environmental Practices. Although Consumer Knowledge does not show a significant direct effect, the application of digital technology and funding of green projects generally contribute positively to financial results. This study also identified that the integration of environmentally friendly practices can improve operational efficiency and brand reputation, as well as meet the demands of consumers who are increasingly concerned about environmental issues. These findings provide strategic guidance for companies to optimize sustainable marketing practices and achieve long-term benefits.